Patterns in University Applications: Socioeconomic Status, Gender, and Subject vs. Institution Preferences - Friederike Hertweck; Robbie Maris; Mirco Tonin; Michael Vlassopoulos (Institute of Labor Economics (IZA), 2025)
This paper examines university application patterns in the UK, focusing on the joint decision of selecting both an institution and a subject. Using administrative data from the Universities and Colleges Admissions Service (UCAS) covering almost all undergraduate applications between 2008 and 2021, we document three key facts: (i) students generally choose subject before university: they apply on average to around 1.6 subject areas across 4.6 institutions, and roughly half apply to a single field across multiple universities; (ii) there are significant gender gaps in application and offer rates that reflect field composition; (iii) high-socioeconomic status students submit more applications, apply less to local institutions, and obtain more offers, but these differences shrink sharply once we control for attainment and the selectivity of the programmes that students apply to. An expert survey suggests that several of these patterns run against conventional wisdom.
Keywords: I20; I23; M38; 330; higher education; application patterns; UCAS data; gender; socioeconomic status